Pengaruh Kegiatan Menggunting Kertas Terhadap Motorik Halus Anak Kelompok A Di TK GKPI Tarutung Kota - Krisna Banurea (Asosiasi Riset Ilmu Pendidikan Indonesia, 2023)
One activity that can improve children's fine motor skills is cutting. The scissor activity aims to train eye coordination and hand muscles as well as concentration. Cutting can be a child's initial preparation stage for writing, especially when holding a pencil. The cutting activity is one of the stimuli that can be developed by educators in developing children's motor skills, especially children's fine motor skills. Children will be able to coordinate their eye senses and hand activities through cutting activities. The aim of this research is to determine the significant influence of paper cutting activities on the fine motor skills of group A at GKPI Tarutung City Kindergarten. The method used in this research is a quantitative descriptive research method. The population is all group A children in the GKPI Tarutung City Kindergarten, totaling 20 people. The improvement in children's fine motor skills can be seen from the children's accuracy in the indicators for variables paper on fine motor skills of group A children at GKPI Tarutung City Kindergarten = 36.5%. Thus, Ha, that is, there is a significant influence of paper cutting activities on the fine motor skills of group A at GKPI Tarutung City Kindergarten, is accepted and H0 is rejected.